A APRENDIZAGEM ORGANIZACIONAL E FORMAÇÃO DO SUCESSOR: UM ESTUDO DE CASO DA LOJA BARRETO - Silva, Alessandro Machado (2010)
This thesis presents a study that investigates the formation of a successor in family business, and the Loja Bareto, located in the Alagoinhas / BA, the unit of empirical study. In this paper, we usually presents as happens in the training and learning in a family business successor. Besides this general goal, we present, more specifically, to describe the family business and its particular characteristics and explore the specific learning and training of successors in family firms. In the section devoted to the methodology gave emphasis to the methodological procedure adopted was that of simple case study, which appears as more appropriate to investigate whether a context where the focus is on contemporary phenomena, embedded in real life situations. Used as tools of data collection the semi structured interview, observation and analysis of external documents. For the data analysis was developed an analytical framework which sought, through the theoretical framework of this thesis, present the relationship between the formation of successor in family firms and individual approaches, cognitive and social practice of organizational learning. We note that for successful succession process, it is necessary for the formation of the successor is not confined to academic training, but mainly through learning the day-by-day organization. In this sense, highlights the importance of organizational learning, especially that of their social and practical, as vital to this process of formation of the successor.